PERAN DAN STRATEGI PENGUATAN KELEMBAGAAN DALAM PENINGKATAN PRODUKSI KELAPA (Cocos nucifera) UNTUK MENDUKUNG PROGRAM KAMPUNGKELAPA MAJENE - Muhsin, Muhsin; Kaimuddin, Kaimuddin; Arsyad, Muhammad; Amran, Arman (Agros Journal of Agriculture Science, 2024)
This research aims to identify the main structures and actors in strengthening existing coconut development institutions in Majene in support of the Majene Coconut Village Program and determining strategic programs to increase coconut production in Majene Regency. This research will be carried out in Majene Regency, West Sulawesi. This research uses Interpretative Structural Modeling (ISM) analysis which functions to formulate complex policy structures based on elements, formulate a hierarchy of relationships between elements, and classify elements into 4 quadrants (autonomous, independent, dependent, and linkage). The result is that the institutions that are key actors in increasing coconut production in Majene Regency are farmer groups/gapoktan, the Livestock and Plantation Agriculture Service, coconut farmers and agricultural extension workers. Then the key programs to increase coconut production are extending plantation land, increasing human resources for extension workers, providing access to capital and standardizing coconut products and their derivatives. The three key programs to increase coconut production also have links with key actors. The extension program is a mandatory program for the Livestock and Plantation Service, with one of its activities being holding field schools. Apart from that, the program to increase human resources for extension workers as a key program is considered very relevant to the conditions faced by extension workers in Majene because the Department of Agriculture, Livestock and Plantation has limited human resources to carry out extension work, they need help from agricultural instructors but are hampered by background knowledge and differences. main duties. Based on institutional analysis, the role of agricultural institutions can be identified in increasing coconut production in various aspects. First, social and institutional roles play a role in forming coordination flows between institutions so that the implementation of programs to increase coconut production can be well organized and achieve targets. Apart from that, institutions also play a role in empowering farmer groups so as to raise their motivation, awareness and involvement in extension activities which will ultimately increase cocoa production through the implementation of GAP. Furthermore, regarding the economic role, institutions play a role in providing production inputs to farmer groups which can have a direct impact in increasing production as well as providing a market for farmers to sell their cocoa through partnerships with companies and NGOs. Then regarding the role of the environment, agricultural institutions strive to cultivate cocoa which produces large and sustainable production through the use of organic fertilizers and pesticides. Keywords: Strategy, improvement, production, coconut IntisariPenelitian ini bertujuan mengidentifikasi struktur dan aktor utama dalam penguatan kelembagaan pengembangan kelapa yang ada di Majene dalam mendukung Program Kampung Kelapa Majene dan menentukan program strategis untuk meningkatkan produksi kelapa di Kabupaten Majene. Penelitian ini akan dilaksanakan di Kabupaten Majene Sulawesi Barat. Penelitian ini menggunakan analisis Interpretative Structural Modelling (ISM) yang berfungsi untuk merumuskan struktur kebijakan yang kompleks berdasarkan elemen, merumuskan hierarki hubungan antar elemen, dan mengklasifikasikan elemen ke dalam 4 kuadran (autonomous, independent, dependent, dan linkage). Hasilnya adalah lembaga yang merupakan aktor kunci dalam meningkatkan produksi kelapa di Kabupaten Majene adalah kelompok tani/gapoktan, Dinas Pertanian Peternakan dan Perkebunan, petani kelapa dan penyuluh pertanian. Kemudian program kunci untuk meningkatkan produksi kelapa adalah ekestensifikasi lahan perkebunan, peningkatan SDM penyuluh, penyediaan akses terhadap modal dan standarisasi produk kelapa dan turunannya. Ketiga program kunci untuk meningkatkan produksi kelapa juga memiliki keterkaitan dengan aktor kunci. Program penyuluhan adalah program wajib bagi Dinas Peternakan dan Perkebunan dengan salah satu kegiatannya yakni mengadakan sekolah lapang. Selain itu, program peningkatan SDM penyuluh sebagai program kunci dinilai sangat relevan dengan kondisi yang dihadapi penyuluh di Majene dikarenakan pihak Dinas Pertanian Peternakan dan Perkebunan memiliki SDM yang terbatas untuk melakukan penyuluhan, mereka membutuhkan bantuan dari penyuluh pertanian akan tetapi terkendala dengan latar belakang pengetahuan dan perbedaan tupoksi. Berdasarkan analisis kelembagaan, maka dapat diidentifikasi peran kelembagaan pertanian untuk meningkatkan produksi kelapa dalam berbagai aspek. Pertama, peran sosial, kelembagaan berperan dalam membentuk alur koordinasi antar lembaga sehingga pelaksanaan program untuk meningkatkan produksi kelapa dapat terorganisir dengan baik dan mencapai sasaran. Selain itu, kelembagaan juga berperan dalam memberdayakan kelompok tani sehingga membangkitkan motivasi, kesadaran, dan keterlibatan mereka dalam kegiatan penyuluhan yang pada akhirnya akan meningkatkan produksi kakao melalui penerapan GAP. Selanjutnya pada peran ekonomi, kelembagaan berperan dalam menyediakan input produksi kepada kelompok tani yang dapat memberikan dampak langsung dalam peningkatan produksi serta memberikan pasar bagi petani untuk menjual kakaonya melalui kemitraan dengan perusahaan dan LSM. Kemudian pada peran lingkungan, kelembagaan pertanian mengupayakan budidaya kakao yang menghasilkan produksi yang banyak serta berkelanjutan melalui penggunaan pupuk dan pestisida organik. Kata Kunci : Strategi, peningkatan, produksi, kelapa